Temperature and GA3 as Modulating Factors in the Biosynthesis of Alkaloids during Imbibition and Early Development of Annona x atemoya Mabb. cv. ‘Gefner’ Seedlings - da Silva, Gustavo Cabral [UNESP]; de-la-Cruz-Chacón, Ivan; Honório, Ana Beatriz Marques [UNESP]; Martin, Bruna Cavinatti [UNESP]; Sousa, Marília Caixeta [UNESP]; Campos, Felipe Girotto [UNESP]; Boaro, Carmen Sílvia Fernandes [UNESP]; Ferreira, Gisela [UNESP] (MDPI, 2022)
Alkaloids are products of the specialized metabolism of plants and temperature is a factor capable of modulating their biosynthesis. Species of the Annonaceae family biosynthesize alkaloids and present dormancy in their seeds, which can be overcome with the use of gibberellins. Therefore, the aim of this work was to evaluate whether temperature variations and the use of gibberellin in seeds affect the production of alkaloids during germination and early development of Annona x atemoya Mabb. cv. ‘Gefner’ seedlings. Results showed that the temperature of 30 °C associated with imbibition in water caused an increase in the production of total alkaloids and liriodenine and that the use of gibberellin decreased production. In addition, it was possible to identify the presence of nine other alkaloids with organ-specific distribution. The presence of none of them was induced by the effect of temperature or gibberellic acid. Therefore, it could be concluded that temperature variation and the use of GA3 alter the biosynthesis of alkaloids, with high temperature causing increased concentration, but the use of GA3 reducing production.
Keywords: annonaceae; benzylisoquinoline alkaloids; gibberellic acid; imbibition; liriodenine; plant regulators